Functional analysis of Mig1 and Rag5 as expressional regulators in thermotolerant yeast Kluyveromyces marxianus - Mochamad Nurcholis (2018)
© 2018, Springer-Verlag GmbH Germany, part of Springer Nature. To analyze the glucose repression mechanism in the thermotolerant yeast Kluyveromyces marxianus, disrupted mutants of genes for Mig1 and Rag5 as orthologs of Mig1 and Hxk2, respectively, in Saccharomyces cerevisiae were constructed, and their characteristics were compared with those of the corresponding mutants of S. cerevisiae. MIG1 mutants of both yeasts exhibited more resistance than the corresponding parental strains to 2-deoxyglucose (2-DOG). Histidine was found to be essential for the growth of Kmmig1, but not that of Kmrag5, suggesting that MIG1 is required for histidine biosynthesis in K. marxianus. Moreover, Kmrag5 and Schxk2 were more resistant than the corresponding MIG1 mutant to 2-DOG, and only the latter increased the utilization speed of sucrose in the presence of glucose. Kmrag5 exhibited very low activities for gluco-hexokinase and hexokinase and, unlike Schxk2, showed very slow growth and a low level of ethanol production in a glucose medium. Furthermore, Kmrag5, but not Kmmig1, exhibited high inulinase activity in a glucose medium and exhibited greatly delayed utilization of accumulated fructose in the medium containing both glucose and sucrose. Transcription analysis revealed that the expression levels of INU1 for inulinase and GLK1 for glucokinase in Kmrag5 were higher than those in the parental strain; the expression level of INU1 in Kmmig1 was higher, but the expression levels of RAG1 for a low-affinity glucose transporter in Kmmig1 and Kmrag5 were lower. These findings suggest that except for regulation of histidine biosynthesis, Mig1 and Rag5 of K. marxianus play similar roles in the regulation of gene expression and share some functions with Mig1 and Hxk2, respectively, in S. cerevisiae.